Description of new species of Resachus Delève, 1968 (Coleoptera: Limnichidae) - Matsumoto, Keita (Zootaxa, 2020)
There are 55 valid species and 8 genera of Afrotropical Limnichidae currently described (Delève, 1968; Spangler et. al. 2001; Hernando & Ribera, 2006; Hernando & Ribera, 2014). Resachus Delève is within the “Mandersia group of genera” according to Hernando & Ribera (2005) with 3 known species: Resachus lineatifrons Delève, 1968 [Democratic Republic of Congo, Zambia]; Resachus schuhi Hernando & Ribera, 2006 [Madagascar]; Resachus striatellus Delève, 1968 [Democratic Republic of Congo, Nigeria] (Delève, 1968; Hernando & Ribera, 2006). Specimens from Malawi have been identified as a new species. The new species have morphological characters, described in this paper, that distinguish them from any other known Resachus.